2011
DOI: 10.1111/j.1471-0528.2010.02847.x
|View full text |Cite|
|
Sign up to set email alerts
|

Saving Mothers’ Lives: Reviewing maternal deaths to make motherhood safer: 2006–2008

Abstract: In the triennium 2006-2008, 261 women in the UK died directly or indirectly related to pregnancy. The overall maternal mortality rate was 11.39 per 100,000 maternities. Direct deaths decreased from 6.24 per 100,000 maternities in 2003-2005 to 4.67 per 100,000 maternities in 2006–2008 (p = 0.02). This decline is predominantly due to the reduction in deaths from thromboembolism and, to a lesser extent, haemorrhage. For the first time there has been a reduction in the inequalities gap, with a significant decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
208
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,148 publications
(222 citation statements)
references
References 2 publications
4
208
0
4
Order By: Relevance
“…Immunosuppression is known to make women more susceptible to severe infection1, 2, 34, 35 and anaemia has been increasingly highlighted as a potential risk factor for severe obstetric complications 9, 13, 31. However, anaemia can be a risk factor, outcome or confounding variable for sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppression is known to make women more susceptible to severe infection1, 2, 34, 35 and anaemia has been increasingly highlighted as a potential risk factor for severe obstetric complications 9, 13, 31. However, anaemia can be a risk factor, outcome or confounding variable for sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent confidential enquiry into maternal deaths has shown that in the UK, the rate of maternal death from genital tract sepsis has decreased substantially from 1.13 to 0.50 deaths per 100 000 maternities (2006–2008 to 2010–2012) 1, 2. However, this promising trend obscures two main issues.…”
Section: Introductionmentioning
confidence: 99%
“…The fifth woman had a concealed pregnancy and laboured and died alone at home. 22 So, none of these women fall into the category of 'normal, healthy women with normal haemoglobins who are at low risk to haemorrhage.' It would thus be fair to say that PPH is not a major cause of maternal mortality among low-risk women cared for by skilled clinicians in high income countries, and that there is no reason why such women should not be cared for expectantly in the third stage.…”
mentioning
confidence: 99%
“…1 Life-threatening blood loss is the primary indication for 95.6% of emergency hysterectomies in labour. 2 Haemorrhage is the most common cause for maternal critical care admission [3][4][5] and places a profound health burden on the childbearing population during an important life event.…”
Section: Haemorrhage and Caesarean Sectionmentioning
confidence: 99%